2016
DOI: 10.3390/land5040031
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Tropical Forest Biomass by Combining ALOS-2, Landsat 8, and Field Plots Data

Abstract: This research was carried out in a dense tropical forest region with the objective of improving the biomass estimates by a combination of ALOS-2 SAR, Landsat 8 optical, and field plots data. Using forest inventory based biomass data, the performance of different parameters from the two sensors was evaluated. The regression analysis with the biomass data showed that the backscatter from forest object (σ • forest ) obtained from the SAR data was more sensitive to the biomass than HV polarization, SAR textures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…In addition, the shortwave infrared (SWIR) bands of Sentinel-2 and Landsat-7 were used to produce the normalized difference moisture index (NDMI), while the Sentinel-2 specific red-edge bands were used to produce inverted red-edge chlorophyll Index (IRECI). The C-band VV-polarization from Sentinel-1, as well as the L-band HH and HV polarizations from ALOS-2 PALSAR-2, were used to acquire backscatter intensities [35,56] and to calculate forest-specific backscatter (FB) values [56]. Vegetation indices were calculated for a 3 m × 3 m raster of pixels of Planetscope, for 10 m × 10 m raster pixels of Sentinel-2 10 m bands, as well as for 20 m × 20 m raster pixels of Sentinel-2 red-edge bands.…”
Section: Satellite Remote Sensing-derived Vegetation Indices and Backmentioning
confidence: 99%
“…In addition, the shortwave infrared (SWIR) bands of Sentinel-2 and Landsat-7 were used to produce the normalized difference moisture index (NDMI), while the Sentinel-2 specific red-edge bands were used to produce inverted red-edge chlorophyll Index (IRECI). The C-band VV-polarization from Sentinel-1, as well as the L-band HH and HV polarizations from ALOS-2 PALSAR-2, were used to acquire backscatter intensities [35,56] and to calculate forest-specific backscatter (FB) values [56]. Vegetation indices were calculated for a 3 m × 3 m raster of pixels of Planetscope, for 10 m × 10 m raster pixels of Sentinel-2 10 m bands, as well as for 20 m × 20 m raster pixels of Sentinel-2 red-edge bands.…”
Section: Satellite Remote Sensing-derived Vegetation Indices and Backmentioning
confidence: 99%
“…If this is the case, then more precise interpretations of forest status can be visualized spatially, leading to better estimation of parameters such as AGB. This method could shed light on relationship analyses made with satellite data (e.g., SAR data), in which it is usually mentioned that collecting actual ground data for relationship analysis with forest parameters is better at larger sample sizes (e.g., 1 ha) to avoid bias; however, collecting such data in large areas at multiple locations is a very time-consuming and difficult task [47]. For example, Němec [11] showed that forest inventory field work, covering a 200 ha area with plot dimensions of 2000 m × 1000 m, required 14 people working for 25 days using calipers and laser rangefinders to measure DBH and tree height, respectively.…”
Section: Forest Parameter Extraction Using Uasmentioning
confidence: 99%
“…Acredita-se que esse melhor resultado esteja relacionado ao tipo de vegetação estudada, ou seja, a saturação da banda C é determinada primariamente pela densidade da vegetação que no estudo foram os mangues, caracterizado por ser uma fitofisionomia que difere no seu grau de densidade com a floresta Amazônica, portanto possibilita melhor desempenho dos estimadores. Nguyen et al (2016) mapearam a biomassa de floresta decídua e tropical no Vietnã. Utilizaram de dados oriundos do satélite Landsat 8 e Alos-2 (banda L), bem como subprodutos oriundos desses satélites (textura, NDVI), além de dados de inventario.…”
Section: Huber Bisquareunclassified
“…O menor RMSE observado pelos autores foi de 35,18 Mg.ha -1 , para uma média de 136 Mg.ha -1 na floresta decídua e 309 Mg.ha -1 para floresta tropical, representando 25% e 11% de erro, respectivamente. Ao comparar a amplitude do erro relativo encontrado por Nguyen et al (2016), os resultados do presente estudo estão dentro da amplitude de valores (16%).…”
Section: Huber Bisquareunclassified